A METHOD OF ELECTROLESS DEPOSITION - NOMA TAKASHI; ISHIBE SHINZO (2024)
무전해 증착 방법의 구현예는, 제1 가장 큰 평면 표면 및 제2 가장 큰 평면 표면을 포함하는 반도체 기판을 제공하는 것; 제2 가장 큰 평면 표면 상에 백메탈 층을 형성하는 것; 백메탈(backmetal) 층 위에 테이프를 부착하는 것; 및 제1 가장 큰 평면 표면 상에 포함된 패드 상에 금속 층을 무전해 증착하는 것을 포함할 수 있다. 방법은 무전해 증착 후, 테이프를 제거하는 것; 및 테이프를 제거한 후, 반도체 기판을 베이킹하는 것을 포함할 수 있다. Implementations of a method of electroless deposition may include providing a semiconductor substrate including a first largest planar surface and a second largest planar surface; forming a backmetal layer on the second largest planar surface; attaching a tape over the backmetal layer; and electroless depositing a metal layer on a pad included on the first largest planar surface. The method may include, after electroless depositing, removing the tape; and after removing the tape, baking the semiconductor substrate.